PENGEMBANGAN MEDIA PRAKTIKUM MENGGUNAKAN HIDROPONIK RAKIT APUNG PADA MATERI PERTUMBUHAN DAN PERKEMBANGAN - Yustanty, Tiara; Daningsih, Entin; Marlina, Reni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstrac This research aimed to know the feasibility of static and dynamic floating raft hydroponics with different nutrient ratios on a medium learning for laboratory work that influenced plant growth. The type of research was research and development (RnD) consisting of six stages namely potential and problems, data collection, design production, validation of design, revision of design, and limited trial. This reserch was modified by adding media validation stage. The validation and student response questionnaire together with student laboratory worksheet was a research instruments. To know feasibility of laboratory work media floating raft hydroponics, then validation was done by media and materials expert. The results of floating raft hydroponic prototype and media validation by media and material experts were categorized as feasible with a percentage of 100%. Based on the results of the student response questionnaire show that students strongly agreed to hydroponic floating rafts used as laboratory work media with a percentage of 92.36%. Keywords: Laboratory Work Media, Hydroponic, Feasibility, Responses